Comparative Epistemology of Al-Farabi and Al-Kindi in the Contextualization of Modern Knowledge - Masykur, Zein Muchamad (Journal of Indonesian Islamic Studies, 2025)
This study examines the comparative epistemology of Islam in the thought of Al-Farabi and Al-Kindi, focusing on its relevance to modern knowledge contexts. Employing a qualitative approach with textual and comparative analysis methods, the study reconstructs the nature of knowledge, reasoning methods, and contextual implications of both philosophers. Al-Farabi emphasizes rational autonomy through the concept of the active intellect, viewing reason as a bridge to divine truth, while Al-Kindi prioritizes the supremacy of revelation asin the ultimate source of truth, with reason serving theology. The analysis reveals that the dialectic of reason and revelation in their thought reflects the intellectual dynamics of classical Islam, capable of addressing modern challenges such as positivism, relativism, and epistemic pluralism. Al-Farabi’s approach is relevant for enriching the philosophy of science and technological ethics, whereas Al-Kindi’s eclectic method offers a model for integrating global knowledge without losing Islamic identity. Their synthesis yields a holistic epistemology that integrates rationality, spirituality, and ethics, capable of engaging global discourses while remaining rooted in tawhid. This study affirms that the epistemologies of Al-Farabi and Al-Kindi are not merely historical artifacts but living sources of inspiration for formulating an inclusive and transformative vision of knowledge in the modern era.